2019
DOI: 10.1021/acsami.8b21766
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Activatable CuS Nanodots to Treat Multidrug-Resistant Bacteria and Release Copper Ion to Accelerate Healing of Infected Chronic Nonhealing Wounds

Abstract: Chronic nonhealing wounds have imposed serious challenges in the clinical practice, especially for the patients infected with multidrug-resistant microbes. Herein, we developed an ultrasmall copper sulfide (covellite) nanodots (CuS NDs) based dual functional nanosystem to cure multidrug-resistant bacteria-infected chronic nonhealing wound. The nanosystem could eradicate multidrug-resistant bacteria and expedite wound healing simultaneously owing to the photothermal effect and remote control of copper-ion relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 52 publications
2
159
0
Order By: Relevance
“…As shown in Figure 1, the synergistic action of the photothermal effect of the CuS nanodots and the release of copper ions produced a robust bactericidal effect on ESBL E. coli and MRSA in vitro. Further in vivo experiments used an MRSA-infected circular wound with a diameter of 0.7 cm in diabetic mice, and found that the experimental group basically healed after 12 days (Qiao et al, 2019).…”
Section: Anti-infectionmentioning
confidence: 99%
“…As shown in Figure 1, the synergistic action of the photothermal effect of the CuS nanodots and the release of copper ions produced a robust bactericidal effect on ESBL E. coli and MRSA in vitro. Further in vivo experiments used an MRSA-infected circular wound with a diameter of 0.7 cm in diabetic mice, and found that the experimental group basically healed after 12 days (Qiao et al, 2019).…”
Section: Anti-infectionmentioning
confidence: 99%
“…Importantly, these two capacities were both pH dependent and could be simultaneously activated by visible light in the presence of a photoacid. In previous reports, 19,26 CuS NPs exhibited signicant antibacterial activity due to their photothermal conversion performance. In our experiments, we demonstrated that CuS NPs could also showed the excellent antibacterial capability through exerting their enzyme mimicking activity.…”
Section: Resultsmentioning
confidence: 94%
“…This element has been demonstrated to increase the expression of TGF-β1 in ex vivo skin models, thus leading to higher pro-collagen 1 and elastin production by fibroblasts [ 67 ]. Moreover, Cu has been demonstrated to enhance skin cell migration (keratinocytes and fibroblasts), which is crucial for wound healing [ 68 , 69 ]. ALIPS9 and ALIG30@10 were shown to favor fibroblast migration in a previous study [ 17 ], which could be related to copper release.…”
Section: Discussionmentioning
confidence: 99%